2003
DOI: 10.1007/s00122-002-1132-9
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of the A locus for the presence of anthocyanin and fs10.1, a major fruit-shape QTL in pepper

Abstract: The purple color of the foliage, flower and immature fruit of pepper ( Capsicum spp.) is a result of the accumulation of anthocyanin pigments in these tissues. The expression of anthocyanins is controlled by the incompletely dominant gene A. We have mapped A to pepper chromosome 10 in a Capsicum annuum (5226) x Capsicum chinense (PI 159234) F(2) population to a genomic region that also controls anthocyanin expression in two other Solanaceous species, tomato and potato, suggesting that variation for tissue-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 25 publications
2
54
0
Order By: Relevance
“…Nevertheless, the genes controlling this variation have not yet been identified. We recently mapped A to pepper chromosome 10 in a region that corresponds to the chromosomal regions containing ag in tomato, F and I in potato and a major gene for the presence of anthocyanin in eggplant fruit (Ben Chaim et al 2003;Doganlar et al 2002;Pillen et al 1996), indicating that these loci are likely to be orthologous. The mapping of structural and regulatory genes of the anthocyanin biosynthetic pathway in tomato indicated that Petunia An2 mapped to chromosome 10, to the same region where the A locus mapped in pepper (Ben Chaim et al 2003).…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, the genes controlling this variation have not yet been identified. We recently mapped A to pepper chromosome 10 in a region that corresponds to the chromosomal regions containing ag in tomato, F and I in potato and a major gene for the presence of anthocyanin in eggplant fruit (Ben Chaim et al 2003;Doganlar et al 2002;Pillen et al 1996), indicating that these loci are likely to be orthologous. The mapping of structural and regulatory genes of the anthocyanin biosynthetic pathway in tomato indicated that Petunia An2 mapped to chromosome 10, to the same region where the A locus mapped in pepper (Ben Chaim et al 2003).…”
Section: Introductionmentioning
confidence: 96%
“…In the case of pepper, genes controlling anthocyanin biosynthesis have been mapped to chromosome 10. Both A and Fc were mapped in the same position of chromosome 10, suggesting that they are allelic (Chaim et al, 2003).…”
Section: Genetic Background Of Anthocyanin Biosynthesismentioning
confidence: 98%
“…There are various species of Capsicum spp. which show anthocyanin pigmentation not only in their fruits but in the flowers and foliage as well , however flower organs are rarely coloured (Chaim et al, 2003). Although, in a mutant collection comprising of almost 400 mutations maintained by Gábor Csilléry ( Figure 1) different vegetative and generative organs show anthocyanin colouration ( Figure 2) (Csilléry, 2016b, a).…”
Section: Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also looked into fruit-related traits (Lefebvre et al, 1998;Ben Chaim et al, 2001b;Chaim et al, 2003;Rao et al, 2003;Wang et al, 2004;Zygier et al, 2005;Ben Chaim et al, 2006b;Lee et al, 2008;Barchi et al, 2009). Results from these studies revealed clusters of QTLs on chromosomes 2, 3 and 4 for fruit traits such as fruit weight/yield, diameter, length and shape.…”
Section: Introductionmentioning
confidence: 99%